2017
DOI: 10.1080/21655979.2017.1283459
|View full text |Cite
|
Sign up to set email alerts
|

Structure and bioactivities of a polysaccharide isolated from Ganoderma lucidum in submerged fermentation

Abstract: In this study, a Ganoderma lucidum polysaccharide GLP-1-1 was isolated from a culture broth with Mw of 22014 Da. Monosaccharide contained glucose, mannose, and galactose with mole percentages of 92.33%, 7.55%, and 0.22%, respectively. Moreover, FTIR and methylation analysis were conducted to characterize the structural properties of GLP-1-1. The results of antioxidant activity analysis showed that GLP-1-1 had a great DPPH and ABTS radical scavenging activity. Meanwhile, GLP-1-1 also exhibited anti-tumor activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In addition, glycosidic bonds might be also represented in the relatively weak absorption peaks at 1620 cm −1 [ 35 ]. Moreover, the stretching vibration of 879 cm −1 referred to the absorption of β -D-glucose with the pyranose form [ 35 , 36 ]. The other bands observed at 1086, 1044, and 879 cm −1 were characteristic absorptions of to β -(1,3), (1,6)-D-glucan [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, glycosidic bonds might be also represented in the relatively weak absorption peaks at 1620 cm −1 [ 35 ]. Moreover, the stretching vibration of 879 cm −1 referred to the absorption of β -D-glucose with the pyranose form [ 35 , 36 ]. The other bands observed at 1086, 1044, and 879 cm −1 were characteristic absorptions of to β -(1,3), (1,6)-D-glucan [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“… Antifungal, Antioxidant, and Antiviral [ 182 , 183 ] 14 Craterellus cornucopioides black chanterelle, black trumpet, trumpet of the dead. North America, Europe, Japan, and Korea Antioxidant, Anti-hyperglycemic, Anti-inflammatory, Antimicrobial, and Immunomodulatory [ 184 , 185 ] 15 Craterellus tubaeformis yellow foot, winter mushroom, or funnel chanterelle Northern America, Europe, and Asia Anti-inflammatory and Antioxidant [ 186 , 187 ] 16 Flammulina velutipes Enokitake velvet shank, golden needle mushroom, or winter mushroom China, Japan, Korea, and Taiwan Antioxidant, Anticancer, Antihypertensive, Antimicrobial, immunomodulatory, and hepatoprotective [ 188 , 189 ] 17 Ganoderma lucidum Lingzhi (Ling chih)/Reishi Malaysia, China, Japan and South Korea Antioxidant, antitumor, Anti – androgenic and cardioprotective [ 190 ] 18 Grifola frondosa Hen of the Wood/Maitake Japan, China Europe and North America Antioxidant, Anti-diabetic, Anti-tumor, Immunomodulatory, antimicrobial, and hepatoprotective [ 116 , 191 ] 19 Gyromitra esculenta Brain mushroom, turban fungus, elephant ears, beefsteak mushroom Britain, Ireland, Europe, and North America Antioxidant, Anticholinesterase, and Antimicrobial [ 192 ,...…”
Section: Edible Mushroomsmentioning
confidence: 99%
“…Numerous studies have shown that EGT, Ganoderma polysaccharides and phenolic substances have strong antioxidant activities. 21,43–47 Ganoderma triterpenoids have strong antitumor 48 and neuroprotective functions, 49,50 and also have the functions of protecting the liver, intestines, 51 and kidneys, 52 and regulating their related metabolism. 53 Ganoderma proteins have antioxidant, melanin inhibition and antibacterial functions, 54 and can protect DNA from hydroxyl radical damage.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown that EGT, Ganoderma polysaccharides and phenolic substances have strong antioxidant activities. 21,[43][44][45][46][47] Ganoderma triterpenoids have strong antitu-…”
Section: Content Of Functional Components In Gswmentioning
confidence: 99%